Competency and improvement needs of clothing and textiles students in body measurement for large scale garment production in Nigeria - Juliana Ego Azonuche; Favour Emelie Afam-Osia; Obioma Angela Adilo; Comfort Ukrajit Sonye (Greenation Publisher & Yayasan Global Research National, 2025)
This study examined the competency and improvement needs of clothing and textiles students in body measurement for large scale garment production in Nigeria. The purpose of the study was to determine the demographic profile, competency improvement needs in illustration of styles and body measurement. Three research questions and hypotheses guided the study respectively. Ex post facto research design was adopted using survey method. Population size was 363students in four tertiary institutions in Anambra State and due to the manageable size of the respondents, there was no sample and all the students were used for the study. Instrument for data collection was structured questionnaire and dad was analyzed with frequency counts, percentages, mean () scores, Standard Deviation (SD), Improvement Need Index (INI), and t-test statistical tools. Findings showed that more females engage in its teaching and learning Clothing and textiles area of specialization while there were few male students. Findings also shows that students have high improvement needs for all the competencies on illustration of styles and 11 competencies on body measurement for large scale garment production. There was no significant difference between the mean () need ratings of male and female students in illustration of styles and body measurement for large scale garment production It was concluded that it is important that fashion designers needs competency improvement for optimal productivity. Therefore, it became imperative that more males be encouraged to enroll in this skill oriented vocational course by giving them scholarship and grants, and well-equipped modern laboratories for skill acquisition and mastery.